EXPRESSION OF ETHNIC BELONGING IN THE UZBEK FOLK ULANS (Scientific journal of the Fergana State University, 2023)
It is known from sources that the Uzbek nationality consists of ninety-two clans. In particular, the nation includes: yapalok, samarchuk, kochartop, boytop, kalmaktop, katagon, jagalboili, suvti, oytamgali, beshtamgali, koshtamgali, saritamgali, argin, kebanak, chilikchi, chilkor, karasyrak, kasar, tortuvli, bolgali, kaitmas, sanam, sheika, galabotir, junbash, representatives of the obiz, mongol, boronchi, eivalak, kerovchi, tama, telov, tarakli, chisels and others. The article provides information about such clans as Sart, Kyrk, Yuz, Nogai, presents the names of the way of life, life, way of life and customs of which are reflected in their composition, as well as their poetic functions in the genre.In conclusion, we can say that:- in ulans, emphasizing ethnicity, it is understood to which clan, nation or people the singers (lancers performers) belong;- specific national features, customs and values, mentality, upbringing, way of life of a nation or clan are embodied;- the opportunity to study and evaluate samples of creativity from a territorial point of view, through the areas in which ethnicity is expressed, to which region the creators and performers belong, and through local symbols, to determine the characteristic features for a particular region.